Enhancing Student Enrollment through Digital Marketing: An Action Research on Increasing the Visibility at a Language Learning Center in Malaysia - Al-Mashhadani, Abdulrazak F.Shahatha; Hassan, Ahmed Ali; Awang, Hapini; Ariffin, Nor Hapiza Mohd (Sinergi International Journal of Management and Business, 2025)
This action research aims to enhance the enrollment of students in the Language Learning Center (LLC) by increasing its visibility through effective digital marketing strategies. The LLC has faced challenges in boosting enrollment, particularly during the pandemic, and previous marketing endeavors have proven ineffective. The research investigates the disparity between current marketing efforts and the overall visibility of the Institution, with a focus on leveraging digital marketing interventions to address this issue. Building upon previous and current research, digital marketing interventions are proposed as a viable solution for enhancing the LLC's marketing activities and visibility. The Segmentation Targeting Positioning (STP) Model forms the foundation of this action research. Following the implementation of digital marketing interventions, emotionally engaging content in the form of videos and online brochures is produced and disseminated through social media and other communication platforms to foster engagement and attract potential customers to the school. The impact of these interventions on student enrollment is assessed using the pragmatism research method, employing a qualitative approach to address the research objectives. The findings indicate that the digital marketing intervention has positively influenced new student registrations for the LLC. Therefore, future researchers are encouraged to explore digital marketing interventions in similar studies.